Applying academic selection criterion to work-integrated learning programmes: risk management or perpetuating inequality?. Issue 1 (2nd January 2020) - Jackson, Denise
ABSTRACT: This study explores whether academic selection criterion should be imposed on students wishing to participate in work-integrated learning (WIL) during their degree studies. Its conceptual framework addresses the limitations of human capital theory and draws on theories about social and cultural capital to understand the role of WIL in developing individual employability. It explores whether WIL should be open to all students, particularly given those who perform less well academically may be of lower socio-economic status with fewer networks and less developed cultural capital. The relationship between academic course average and workplace performance during WIL was examined, rated by 2012 undergraduates and their workplace supervisors. The more academically successful students displayed greater confidence in their workplace performance yet there was no relationship between academic achievement and workplace performance from the supervisor perspective. The removal of academic selection criterion is recommended and more equitable strategies for recruiting suitable students are discussed.